Labor Demand Response to Labor Supply Incentives: Lessons from the German Mini-Job Reform - Gabriela Galassi (Institute of Labor Economics (IZA), 2021)
This paper analyzes how firms respond to changes in tax benefits for low-earning workers and how such policies also affect high-earning workers. I explore establishment outcomes around Germany's 2003 Mini-Job Reform, which expanded tax benefits for low-earning workers. I document that highly exposed establishments–high proportion of low-earning workers–increase their employees relative to non-exposed establishments–low proportion of such workers. This relative expansion is tilted towards high-earning workers, not targeted by the tax benefits. Nonexposed establishments substitute employment towards low-earning workers without expanding at the same pace. My findings are consistent with a model in which employment growth the policy intended is accompanied by a reallocation of employment and production between highly exposed firms and non-exposed firms, resulting in an efficiency loss.
Keywords: H20; H24; H32; E24; E64; I38; J23; J38; 330; tax benefits; firm decisions; spillovers